A social-political history of monotheism - Cataldo, Jeremiah W., author.
1 online resource
Keywords: "In A Social-Political History of Monotheism, Cataldo shows how political concerns were fundamental to the development of Judeo-Christian monotheism. Beginning with the disruptive and devastating historical events that shook early Israelite culture and ending with the seemingly victorious emergence of Christianity under the Byzantine Empire, this work highlights critical junctures marking the path from political frustration to imperial ideology. Monotheism, Cataldo argues, was not an enlightened form of religion; rather, it was a cultic response to effluent anxieties pouring out from under the crushing weight of successive empires. This provocative work is a valuable tool for anyone with an interest in the development of early Christianity alongside empires and cultures. "--Provided by publisher.